Mental Health Among Displaced People and Refugees : Making the Case for Action at the World Bank Group - Marquez, Patricio V. (World Bank, Washington, DC, 2017)
The current crisis of forced displacement is posing serious humanitarian and development challenges across the world. The World Bank Group and the international community at large cannot ignore these challenges, given their scale and complexity. As documented in a recent World Bank report, about 65 million people – one percent of the world’s population – live in forced displacement and extreme poverty. In contrast to economic migrants, who move in search of better opportunities, and to persons affected by natural disasters, the forcibly displaced are fleeing conflict and violence. Host countries often have limited resources even before taking in refugees. The refugee influx can quickly overwhelm existing capacities, including health, housing, educational, and social welfare systems and services. Inflows of displaced people can cause social and economic challenges and disruptions to host communities. However, refugees can also bring skills, expertise, and labor that can benefit communities in the longer term. The international community can act to reduce vulnerabilities among the forcibly displaced during a crisis and then help them rebuild their lives. Such action can also mitigate the impact of forced displacement on host communities and governments. This requires action to support economic activity, job creation, and social cohesion, as well as to strengthen and expand essential services. Finally as an effective response to the mental health needs of the displaced and refugees would require strengthening partnerships between the World Bank Group (WBG), World Health Organization (WHO), United Nations High Commissioner for Refugees (UNHCR), and other international and national partners, such as Partners in Health (PIH) and International Medical Corps (IMC).